Pengembangan Media Pembelajaran Interaktif Berbasis Adobe Flash Professional CS6 Pada Program Studi Sastra Agama Dan Pendidikan Bahasa Bali STAHN Mpu Kuturan Singaraja - I Nengah Adi Widana; I Nengah Juliawan; Made Suardika Jaya; I Wayan Juliana (Cetta: Jurnal Ilmu Pendidikan, 2022)
Education in Indonesia in March 2020 experienced significant turmoil, this was due to the pandemic caused by Covid-19. Learning that was initially carried out face-to-face, was then carried out online by applying or using more effective learning media. One of them is by using Adobe Flash Professional CS6. The researcher uses a Research and Development (R&D) model with a 4-D (four D) model through the development stages including Define, Design, Develop, and Disseminate. The results showed that the media feasibility level which was validated by equipment experts showed a feasibility level with a percentage of 88.75%. Meanwhile, the feasibility level of the material expert shows the feasibility level with a percentage of 93.75%. The responses given by educators and students are carried out by conducting product trials, then educators and students are asked to fill out a questionnaire using the google form application. As for the results in terms of educators responding with a percentage of 83.13% satisfying and from students getting a response with a percentage of 80.61% satisfactory.